Quality Assessment in Conference and Community Interpreting - Pöchhacker, Franz (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2001)
AbstractOn the assumption that interpreting can and should be viewed within a conceptual spectrum from international to intra-social spheres of interaction, and that high standards of quality need to be ensured in any of its professional domains, the paper surveys the state of the art in interpreting studies in search of conceptual and methodological tools for the empirical study and assessment of quality. Based on a selective review of research approaches and findings for various aspects of quality and types of interpreting, it is argued that there is enough common ground to hope for some cross-fertilization between research on quality assessment in different areas along the typological spectrum of interpreting activity.